2020
DOI: 10.1016/j.jadohealth.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Sexual Minority Youth in Pediatric Primary Care Settings Within a Large Integrated Healthcare System Using Electronic Health Records

Abstract: The aim of the study was to estimate the prevalence of sexual minority youth (SMY) within an integrated health care system using a standardized questionnaire. Methods: This study assessed SMY status in youth aged 12.5e18 years using a previsit Well Check questionnaire at Kaiser Permanente Northern California facilities in 2016. SMY was defined as selfreported attraction to the same sex or both sexes. Results: A total of 93,817 youth (87.3%) self-reported sexual attraction, and 5% (n ¼ 5,329) of respondents (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Our study found that the TGD reporting among adolescents differed by age. Similar to self-report of sexual attraction and orientation, younger adolescents may be less likely to report as TGD because they are exploring their gender identity, unwilling to answer, or simply do not understand the question [18,31]. Tailoring of questions about gender identity by age may be warranted, as well as exploring how best to ask the question about gender to ensure both comfort and gender affirmation (e.g., allowing a patient to identify as "male" or "female" while also indicating they are "transgender").…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study found that the TGD reporting among adolescents differed by age. Similar to self-report of sexual attraction and orientation, younger adolescents may be less likely to report as TGD because they are exploring their gender identity, unwilling to answer, or simply do not understand the question [18,31]. Tailoring of questions about gender identity by age may be warranted, as well as exploring how best to ask the question about gender to ensure both comfort and gender affirmation (e.g., allowing a patient to identify as "male" or "female" while also indicating they are "transgender").…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined approaches to gender identity screening in adolescents. Using a previsit questionnaire to ask adolescents about their sexual health and to screen for psychosocial issues has been found to help normalize and promote discussions of sensitive topics [17,18]. A recent study found that adding a standardized gender identity screening question to a previsit questionnaire increased the documentation of gender identity for adolescents presenting for annual adolescent physicals [19].…”
Section: Implications and Contributionmentioning
confidence: 99%
“…To address this gap between recommendations and practice, some pediatric providers are incorporating questions about sexuality into electronic or other previsit screening tools [4]. In this issue of the Journal of Adolescent Health, Parmar et al [5] are the first to report findings from a large-scale implementation of a standardized assessment of sexual attraction at adolescent health supervision visits.…”
mentioning
confidence: 99%